Intracranial artery dolichoectasia: What should the neurologist know? - Lorena Dellagnesi Depieri; Renan Rodrigues Neves Ribeiro do Nascimento; Lorena Souza Viana (Exploration of Neuroscience)
Intracranial artery dolichoectasia (IADE) is a vascular anomaly characterized by dilation and/or tortuosity of one or more intracranial arteries. While many cases are incidental findings on imaging, the associated ischemic neurological complications of IADE can be severe and must be promptly recognized. This study aims to increase awareness among general practitioners and neurologists regarding this rare and potentially life-threatening condition. We utilized reputable databases for this scoping review, including PubMed, Scopus, and Google Scholar, from database inception through September 2024, using a combination of terms such as “Dolichoectasia of Basilar Artery”, “Intracranial Dolichoectasia”, and “Ischemic Stroke”. Our scoping review revealed that IADE is a challenging and often underdiagnosed condition, with an estimated prevalence of less than 1% in the general population. Hypertension, atherosclerosis, and advanced age are well-documented risk factors. To minimize the risk of misdiagnosis, we briefly elucidated the pathophysiology of IADE, correlating it with clinical and radiological features. We discuss the diagnostic criteria for IADE based on radiological imaging, addressing the advantages and limitations of different techniques. Finally, we highlight the unmet clinical needs related to IADE management, which may involve pharmacological and surgical therapies tailored to individual cases, with careful consideration of safety and efficacy.